Service performance comparison of vibrating wire strain sensors for pipeline - Shengyi SHA; Wenxing FENG; Yiwei ZHAN; Hanqing SUN; Qiming YANG; Chao SUN; Nianfei ZHANG (You-qi chuyun, 2022)
The vibrating wire strain sensors have been widely used in the field of stress and strain monitoring of oil and gas pipelines. However, different types of vibrating wire sensors vary greatly in service performance due to the influence of pipeline operating conditions and installation processes. In order to understand the actual service life of this type of sensors in strain monitoring of oil and gas pipelines and compare the error of monitoring data, the spot-weldable and arc-weldable vibrating wire strain sensors were studied and continuous monitoring was conducted to the stress state of gas pipelines in the goaf area of Qufu Coal Mine. Through comparative analysis to the 12-year continuous monitoring data, it is found that the survival rate of arc-weldable sensors decreases linearly with time, while the error of monitoring data increases linearly, resulting in a large cumulative measuring error. This is because the arc-weldable sensors are installed on the anticorrosive coating, cannot obtain the real stress of pipeline directly, and may fall off due to the influence of the external factors. Compared with the arc-weldable sensors, the spot-weldable sensors can truly reflect the stress-strain state of pipelines with the measurement data, have a longer service life, and meet the requirements of continuous monitoring for the minimum survival rate of sensors.